2006
DOI: 10.18553/jmcp.2006.12.8.656
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Thyroid Monitoring in Ambulatory Patients Prescribed Amiodarone in 10 HMOs

Abstract: he association between amiodarone and liver, thyroid, ocular, cardiac, skin, and pulmonary adverse events has been recognized for more than 20 years. [1][2][3][4][5][6][7][8] Asymptomatic elevation of liver enzymes occurs in 5%-24% of patients prescribed amiodarone, symptomatic liver injury occurs in up to 3%, 4,9 and thyroid dysfunction (including both hyper-and hypothyroidism) occurs in 2% to 24%. [10][11][12] Nearly all cases of liver and thyroid function abnormalities associated with amiodarone therapy are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…A study of 10 managed care organizations in [2003][2004] found that only about one-half of all ambulatory patients on amiodarone received both recommended tests for liver and thyroid function. 10 Bickford and Spencer (2006) measured adherence to the NASPE guideline for baseline monitoring among 45 patients initiated on amiodarone therapy during a hospital admission at a medical university. The authors found that 82% received baseline thyroid function tests, and 87% received baseline liver function tests.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 10 managed care organizations in [2003][2004] found that only about one-half of all ambulatory patients on amiodarone received both recommended tests for liver and thyroid function. 10 Bickford and Spencer (2006) measured adherence to the NASPE guideline for baseline monitoring among 45 patients initiated on amiodarone therapy during a hospital admission at a medical university. The authors found that 82% received baseline thyroid function tests, and 87% received baseline liver function tests.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Laboratory test monitoring was recorded at baseline (up to 6 months before the index date), from 1-6 months after the index date, 7-12 months after the index date, and at any time during the year (months [1][2][3][4][5][6][7][8][9][10][11][12]. Alanine aminotransferase (ALT) was evaluated for liver function.…”
mentioning
confidence: 99%
“…In patients under amiodarone therapy, evaluation of thyroid function is usually recommended at 6-month intervals (1,2,3,24). Based on the present data, we suggest a closer follow-up (i.e.…”
Section: European Journal Of Endocrinologymentioning
confidence: 59%
“…We may have missed monitoring that was done outside of our system, but prior research suggests that this is unlikely. 47 Third, the interviewed patients may not be representative of the whole population (all white and educated); the same barriers that prevent completing testing may also impede appearing for an interview. We attempted to overcome that issue with telephone interviews to reach more patients, but we cannot rule out that we missed patients who had other major barriers to both testing and interviewing.…”
Section: Ged General Education Diplomamentioning
confidence: 99%